Prospects of 3G service: a study on Malaysian customer perspectives - Haque, A. K. M. Ahasanul; Khatibi, Ali; Borucki, Chet; Ab. Yajid, Mohd. Shukri (The Institute for the Management of Information Systems, 2009)
This study focused on identifying factors related to the adoption or rejection of 30 service by consumers in Malaysia. The research findings indicate that age and gender influence the adoption decision. These findings prevailed when age groups view differences in terms of (1) loyalty towards the existing mobile service provider and (2) the perceived greater convenience afthe current 2G/2.5G service. The gender perspective also showed significant differences in terms of the importance to access 30 services and loyalty branding. Cluster analysis was conducted to identify customer groupings based on similarity in patterns ofadoption among consumers. Two cluster groups with different adoption pallerns emerged. Cluster 2 is comprised of a higher income group with the tendency to adopt 30 service since they have the earning capacity whereas cluster 1 is largely of middle income holders. Females represent the majority in cluster 1 whereas cluster 1 is dominated by males.